1970
DOI: 10.1007/bf00388040
|View full text |Cite
|
Sign up to set email alerts
|

Atmungswege bei vernarbenden und proliferierenden Gewebefragmenten der Kartoffelknolle

Abstract: The typical wound respiration drift (O2 und CO2) of 1 mm disks, which amounts to 6 times the values measured immediately after derepression, develops only if cicatrization takes place, but never in proliferating or non-proliferating tissues without suberin biosynthesis. The respiration rate of the latter is merely approximately doubled during the first 8 hours and maintains a steady state level continuously for 6 days. The respiratory drift is not affected by methods of tissue preparation and CO2-concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1970
1970
1992
1992

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Whereas CO2 is normally considered an ethylene antagonist (13), in this case, as with the overcoming of thermodor mancy in lettuce seed (51) and the activation of pea cotyledon ATPase (70), ethylene and CO2 act synergistically. The incentive for CO2 utilization in the context under discussion stemmed from the observations of Lange (58) on the effect of CO2 on the elicitation of CN resistance in aging potato slices, reinforced by the report of McCaig & Hill (73) on the effect of CO2 on the development of CN resistance in wheat seedlings. Lange showed that potato slices aged in 10% CO2 in moist air fully developed a CN-stimulated induced respiration in 12 h, whereas slices aged in aerated solution in conventional fashion became 85% CN resistant in 24 h, and fully eN resistant in 48 h. Of more importance, however, slices aged in high CO2 formed proliferating callus, whereas conventionally aged slices formed ter minal periderm.…”
Section: The Induction Of En-resistant Respiration In Ethylene-treatementioning
confidence: 96%
“…Whereas CO2 is normally considered an ethylene antagonist (13), in this case, as with the overcoming of thermodor mancy in lettuce seed (51) and the activation of pea cotyledon ATPase (70), ethylene and CO2 act synergistically. The incentive for CO2 utilization in the context under discussion stemmed from the observations of Lange (58) on the effect of CO2 on the elicitation of CN resistance in aging potato slices, reinforced by the report of McCaig & Hill (73) on the effect of CO2 on the development of CN resistance in wheat seedlings. Lange showed that potato slices aged in 10% CO2 in moist air fully developed a CN-stimulated induced respiration in 12 h, whereas slices aged in aerated solution in conventional fashion became 85% CN resistant in 24 h, and fully eN resistant in 48 h. Of more importance, however, slices aged in high CO2 formed proliferating callus, whereas conventionally aged slices formed ter minal periderm.…”
Section: The Induction Of En-resistant Respiration In Ethylene-treatementioning
confidence: 96%
“…Guided by observations by Lange (1970) that atmospheres enriched in CO2 favor the development of cyanide resistance in potato slices aged in moist air, we discovered that 10% CO, added to a mixture of ethylene in O, either accentuates the ethylene effect in conditioned tubers (Day et al 1978), or substitutes for the conditioning process (see below). The synergistic effect of Oj on ethylene action has been amply demonstrated (Chin andFrenkei 1977, Theologis andLaties 1982), and attention in what follows centers on the role of CO,.…”
Section: Introductionmentioning
confidence: 91%
“…2). Where slicing is concerned, CO, diverts the development of a terminal periderm in slices to proliferating callus, at the same time that it limits the extent of the wound-induced respiration and hastens the restoration of CN" resistance (Lange 1970). In tubers, ethylene alone creates tubers that yield CN"-resistant fresh siices in conjunction with a respiration climax when conditioned tubers are treated soon after harvest.…”
Section: The Effect Of Lycorine Incubation On Glucose Absorptionmentioning
confidence: 99%
“…Aging presumably dissipates (by metabolism, transport, diffusion, and dilution) endogenous growth regulating substances. It also reduces problems associated with the response of tissues to cutting or tactile stimuli, as wounding or mechanical stimulation cause, in some tissues, a transitory acceleration of growth (4, 6) and respiration (1,8).We have investigated the growth effects of various conditions (both prior to and during growth measurements) on light-grown pea stem segments. With such information, the effects of subsequent treatments can be ascribed with greater confidence to the experimental treatment, not to endogenous conditions.…”
mentioning
confidence: 99%
“…Aging presumably dissipates (by metabolism, transport, diffusion, and dilution) endogenous growth regulating substances. It also reduces problems associated with the response of tissues to cutting or tactile stimuli, as wounding or mechanical stimulation cause, in some tissues, a transitory acceleration of growth (4,6) and respiration (1,8).…”
mentioning
confidence: 99%